Astrophysical Sources of Cosmic Rays and Related Measurements with the Pierre Auger Observatory - Collaboration, TPA; Abraham, J; Abreu, P; Aglietta, M; Aguirre, C; Ahn, E; Allard, D; Allekotte, I; Allen, J; Alvarez-Muñiz, J; Ambrosio, M; Anchordoqui, L; et al. (2009)
Studies of the correlations of ultra-high energy cosmic ray directions with extra-Galactic objects, of general anisotropy, of photons and neutrinos, and of other astrophysical effects, with the Pierre Auger Observatory. Contributions to the 31st ICRC, Lodz, Poland, July 2009.